Estimating the incidence of colorectal cancer in Sub-Saharan Africa: A systematic analysis - Alice Graham; Davies Adeloye; Liz Grant; Evropi Theodoratou; Harry Campbell (Edinburgh University Global Health Society, 2012)
Nearly two-thirds of annual mortality worldwide is attributable to non-communicable diseases (NCDs), with 70% estimated to occur in low- and middle-income countries (LMIC). Colorectal cancer (CRC) accounts for over 600 000 deaths annually, but data concerning cancer rates in LMIC is very poor. This study analyses the data available to produce an estimate of the incidence of colorectal cancer in Sub-Saharan Africa (SSA).